1985
DOI: 10.1042/bj2320061
|View full text |Cite
|
Sign up to set email alerts
|

Decanoyl lysophosphatidic acid induces platelet aggregation through an extracellular action. Evidence against a second messenger role for lysophosphatidic acid

Abstract: Platelets rapidly convert 1,2-didecanoyl-sn-glycerol into its corresponding phosphatidic acid and lysophosphatidic acid derivatives, thereby providing a means of introducing these two compounds into platelets. 1-Decanoyl-2-lyso-3-sn-phosphatidic acid, when added directly to platelets, induced platelet aggregation and raised intracellular Ca2+ levels at concentrations of 0.3 microM upwards, but was without effect when formed intracellularly from 1,2-didecanoylglycerol at an estimated concentration of approx. 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 41 publications
(51 reference statements)
0
34
0
Order By: Relevance
“…Transient rises in blood pressure in rats and guinea pigs after intravenous LPA injection have also been documented (Tokumura et al, 1978). LPA is released by activated platelets and accumulates in serum to low micromolar levels (Schumacher et al, 1979;Simon et al, 1982;Watson et al, 1985). The induction of platelet aggregation and fibroblast recruitment along with its mitogenic capabilities implicate this lipid as a wound healing hormone (Moolenaar, 1995).…”
mentioning
confidence: 99%
“…Transient rises in blood pressure in rats and guinea pigs after intravenous LPA injection have also been documented (Tokumura et al, 1978). LPA is released by activated platelets and accumulates in serum to low micromolar levels (Schumacher et al, 1979;Simon et al, 1982;Watson et al, 1985). The induction of platelet aggregation and fibroblast recruitment along with its mitogenic capabilities implicate this lipid as a wound healing hormone (Moolenaar, 1995).…”
mentioning
confidence: 99%
“…Because activated platelets copiously secrete the mediator, it has been suggested that aggregated platelets are the primary source of the serum LPA (14,18). This source, coupled with the mitogenic and chemotactic properties of LPA, has prompted the hypothesis that the phospholipid is an important mediator of wound healing (12).…”
mentioning
confidence: 99%
“…Extracellular addition of LPA results in increases in [Ca 2ϩ ] i in many cell types, including fibroblasts, platelets, vascular smooth muscle cells, neuronal cells, astrocytes, mesangial cells, many tumor cells, and X. laevis oocytes (Watson et al, 1985;Jalink et al, 1990;Durieux et al, 1992;Inoue et al, 1995;Jalink et al, 1995;Xu et al, 1995;Keller et al, 1997;Seewald et al, 1997). LPAinduced Ca 2ϩ mobilization can be transduced through both PTX-sensitive and PTX-insensitive G protein activation of PLC.…”
mentioning
confidence: 99%